2021
DOI: 10.3126/jnps.v40i3.29412
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Bilirubin Measured by Biliscan (Smartphone Application) in Neonatal Jaundice – An Observational study

Abstract: Introduction: Bilirubin is a frequently ordered investigation in neonatal intensive care units and out-patient practice during follow- up. The gold standard for its estimation is serum bilirubin which is invasive resulting in parenteral apprehension, pain, discomfort and iatrogenic anaemia in a neonate, while the non-invasive measurement by transcutaneous bilirubinometer is not available in all the centres because of its cost. Biliscan is a smartphone application that uses a phone’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
3
7
0
Order By: Relevance
“…Our study showed higher correlation between BsB and TSB among Chinese babies compared to non-Chinese babies with r of 0.65 versus 0.44, respectively. This observation concurs with that of prior validation studies [18][19][20] on the use of Biliscan app. Rong et al validated the use of Biliscan on primarily Chinese infants and showed a higher correlation coefficient of 0.79, whereas Lingaldinna et al 20 and Swarna et al 19 independently applied the Biliscan on Indian babies and obtained the same lower Pearson correlation of 0.6.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study showed higher correlation between BsB and TSB among Chinese babies compared to non-Chinese babies with r of 0.65 versus 0.44, respectively. This observation concurs with that of prior validation studies [18][19][20] on the use of Biliscan app. Rong et al validated the use of Biliscan on primarily Chinese infants and showed a higher correlation coefficient of 0.79, whereas Lingaldinna et al 20 and Swarna et al 19 independently applied the Biliscan on Indian babies and obtained the same lower Pearson correlation of 0.6.…”
Section: Discussionsupporting
confidence: 92%
“…This observation concurs with that of prior validation studies [18][19][20] on the use of Biliscan app. Rong et al validated the use of Biliscan on primarily Chinese infants and showed a higher correlation coefficient of 0.79, whereas Lingaldinna et al 20 and Swarna et al 19 independently applied the Biliscan on Indian babies and obtained the same lower Pearson correlation of 0.6. These suggest that skin pigmentation may have a confounding influence on BsB readings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations